The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1177/2309499016684744
|View full text |Cite
|
Sign up to set email alerts
|

Color Doppler ultrasound assessment for identifying perforator arteries of the second dorsal metacarpal flap

Abstract: Purpose: The second dorsal metacarpal (SDMC) perforator flap has been widely used for the soft tissue reconstruction of the hand. However, it is difficult to identify the depth and branches of the perforators of the second dorsal metacarpal artery (SDMA) using only handheld acoustic Doppler flowmetry (HADF), which is the most common method. The purpose of this study was to compare the results of examination by color Doppler ultrasonography (CDU) with those of HADF and to evaluate the efficacy of CDU for detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…They also described in detail the cutaneous perforators of the second to fourth DMAs, whereas there was no mention of the FDMA, which has the potential for covering more radial defects. Replication studies confirmed the existence of the cutaneous perforators at the level of the second to fourth metacarpal heads [14,15].…”
Section: Discussionmentioning
confidence: 60%
“…They also described in detail the cutaneous perforators of the second to fourth DMAs, whereas there was no mention of the FDMA, which has the potential for covering more radial defects. Replication studies confirmed the existence of the cutaneous perforators at the level of the second to fourth metacarpal heads [14,15].…”
Section: Discussionmentioning
confidence: 60%
“…Many anatomic studies have proven that the first and second dorsal metacarpal arteries are anatomically constant; thus, the flap has a safe pedicle source. The perforator arises just distal to the juncturae tendinum, and because it arises directly from the branches of the deep palmar arch, the DMAP flap can be raised even if there is no dorsal metacarpal artery [13][14][15][16][17]. Sebastin et al [13] defined the indications of the DMAP flap in palmar defects up to the proximal half of the middle phalanx and dorsal defects up to the proximal distal interphalangeal joint.…”
Section: Discussionmentioning
confidence: 99%
“…This report simply extends the literature on this paradigm to include the first webspace region of the hand. Although the present report does not rely on a cadaver study to define perforator locations and dimensions, this FDMA perforator propeller flap is conceptually comparable to DMCA perforator flaps based on metacarpals 2,3 and 4, with its dominant perforator arising at the metacarpal neck [ 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%